Performance analysis of a self-adaptive building integrated photovoltaic thermoelectric wall system in hot summer and cold winter zone of China. (1st December 2017) - Luo, Yongqiang; Zhang, Ling; Liu, Zhongbing; Wu, Jing; Zhang, Yelin; Wu, Zhenghong; He, Xihua
Abstract: The traditional building integrated photovoltaic (BIPV) systems are meeting with their limitations. By incorporating thermoelectric radiant system with PV module, a prototype of building integrated photovoltaic thermoelectric (BIPVTE) wall system is proposed and numerically investigated. The system model of BIPVTE wall is established and validated by experimental data. The comprehensive system performance evaluation is conducted based on the comparison with the traditional PV wall and massive wall in hot summer and cold winter zone of China. The comparison between BIPVTE and PV wall in steady state can explain the system working mechanism as well as its weakness. Besides, the typical-day, seasonal and annual dynamic performance evaluations are implemented for the application potential analysis of BIPVTE in Changsha city and other four typical modern cities. The results indicate that BIPVTE wall can achieve noticeable reduction of annual heating/cooling load. The highest energy saving ratio of 172% compared with the massive wall is achieved under Shanghai weather condition. This system has the potential to make contribution to zero energy buildings and low exergy buildings. Highlights: A system model is established for building integrated photovoltaic wall system. The system model is verified through comparison with experiment result. The system performance of researched system is compared with conventional PV wall. Annual simulations and analysis show high system performance under different weather conditions.